From Input-Output to Output-Only Modal Identification of Civil Engineering Structures - Álvaro Cunha (2005)
This paper presents a brief characterization of the evolution of Experimental Modal Analysis in the Civil Engineering field, from Input-Output to Output-Only Modal Identification Techniques, taking particularly into account the experience of the authors at the Laboratory of Vibrations and Monitoring (VIBEST, www.fe.up.pt/vibest) of FEUP.